2020
DOI: 10.1186/s40249-020-00703-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between obesity and clinical prognosis in patients infected with SARS-CoV-2

Abstract: Background: It is well established that obesity is a disease of sustained low-grade inflammation. However, it is currently unknown if obesity plays a role in the clinical manifestations and prognosis of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infected patients. In this study, we aimed to investigate whether obesity played a role in clinical manifestations and prognosis in patients infected with SARS-CoV-2. Methods: This is a retrospective multicenter clinical study. A total of 96 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 25 publications
3
46
3
1
Order By: Relevance
“…Based on retrospective data from 245 individuals with COVID-19, Liu et al [23] found that the unadjusted association between baseline hemoglobin levels and all-cause mortality during hospitalization was non-significant, and the odds ratio of death with increasing serum hemoglobin level was 0.98 (95% CI 0.96, 1.00, p = 0.05). Cai et al [24] studied factors associated with ICU admission and found no link between hemoglobin levels and odds of being admitted at ICU. In a study by Cen et al [25] hemoglobin levels below 110 g/L were linked with disease progression in patients with COVID-19; univariable hazard ratio was 3.91 (95% CI 2.99-5.10).…”
Section: Serum Hemoglobin Levelsmentioning
confidence: 99%
“…Based on retrospective data from 245 individuals with COVID-19, Liu et al [23] found that the unadjusted association between baseline hemoglobin levels and all-cause mortality during hospitalization was non-significant, and the odds ratio of death with increasing serum hemoglobin level was 0.98 (95% CI 0.96, 1.00, p = 0.05). Cai et al [24] studied factors associated with ICU admission and found no link between hemoglobin levels and odds of being admitted at ICU. In a study by Cen et al [25] hemoglobin levels below 110 g/L were linked with disease progression in patients with COVID-19; univariable hazard ratio was 3.91 (95% CI 2.99-5.10).…”
Section: Serum Hemoglobin Levelsmentioning
confidence: 99%
“…Selected data on obesity and outcome are shown in Table 1. [17][18][19][20][21][22][23] In western countries, although data from Italy have confirmed earlier Chinese reports, 24 a French study showed that patients with BMI > 35 kg/m 2 were at significantly higher risk for the requirement of intensive mechanical ventilation compared to normal-weight individuals (with BMI lower than 25 kg/m 2 ), even after adjusting for age, diabetes and hypertension. 25 These results were later replicated in a different hospital in France 26 and have generated more interest in the association between adipose tissue excess and disease pathophysiology.…”
Section: Epidemiological Datamentioning
confidence: 76%
“…Opposing roles have been attributed to adiponectin and IL-6 vis-a-vis the modulation of insulin sensitivity.Inhibition of adiponectin production by IL-6 and TNF-a, lowers adiponectin levels and perpetuates the low-grade chronic inflammation of metabolic disorders 71,72. It would be reasonable to study levels of these or other adipokines in patients with COVID-19 and assess their clinical utility as biomarkers of disease severity and progression. OBESITY AND CORONOVIRUSES: SPECIFIC MOLECULAR TARGETS AND SHARED PATHOPHYSIOLOGY Gattinoni et al suggested that COVID-19 pneumonia presents with two time-related main phenotypes identified based on CT findings: Type L, characterized by low elastance (ie, high compliance), low ventilation-to-perfusion ratio, low lung weight and low recruitability and Type H, characterized by high elastance, high right-to-left shunt, high lung weight and High recruitability.…”
mentioning
confidence: 99%
“…Os estudos incluídos foram conduzidos no México, China, Estados Unidos e França 10-18 . O tempo de seguimento dos estudos variou de 1 a 2 meses, sendo cinco artigos [11][12][13]16,18 Referente aos parâmetros laboratoriais, como contagem de linfócitos 11,12,18 e de plaquetas foi visto que estes estavam negativamente correlacionados ao IMC, enquanto a contagem de hemoglobina, CK, creatinina sérica e LDH apresentaram correlação significativamente positiva 12 . Além disso, indivíduos obesos apresentam níveis mais altos de PCR, aspartato aminotransferase, glicemia em jejum e LDL 12,18 .…”
Section: Figura 1 Fluxograma Da Triagem E Seleção Dos Artigos Que Inunclassified